A Systematic Literature Review and Bibliometric Analysis of Global Trends in Character Education at the Elementary School Level - Muhammad Isro' Hidayatullah; Melinda Septiani; Hamdiana Hamdiana; Lalu Sumardi; Dadi Setiadi; Rano Zokhidova; Sukron Fujiaturrahman (IJECA (International Journal of Education and Curriculum Application), 2026)
Character education plays a crucial role in developing ethically grounded and socially responsible learners amid contemporary global challenges. However, existing studies remain fragmented, with limited synthesis of global research patterns, methodological orientations, and theoretical developments at the elementary school level. Addressing this gap, this study aims to strengthen the global positioning of character education research through an integrated Systematic Literature Review (SLR) and bibliometric analysis. Guided by PRISMA guidelines, the study reviewed 110 Scopus-indexed journal articles published between 2011 and 2025. Bibliometric analysis was employed to map publication trends, geographic distribution, influential authors, and keyword-based thematic clusters, while thematic synthesis was used to examine research designs, conceptual frameworks, and recurring gaps. Data were retrieved from the Scopus database using a structured screening protocol, and thematic coding was conducted using NVivo with manual cross-validation to ensure analytical rigor. The findings indicate a steady growth in publications, with Asian countries emerging as major contributors. Research themes increasingly emphasize moral education, social–emotional learning, and global citizenship, supported predominantly by qualitative and mixed-method approaches. Nevertheless, the literature remains constrained by context-specific studies, limited longitudinal evidence, and challenges in cross-cultural measurement of character outcomes. The study contributes theoretically by clarifying the evolving conceptual landscape of elementary character education and methodologically by demonstrating the value of integrating bibliometric mapping with thematic synthesis. Practically, the findings offer guidance for developing scalable, context-responsive, and empirically grounded character education models applicable across diverse educational settings.